The short and long-term relation between human development and female unemployment: the case of Turkey - Tatli, Halim; Tasci, Kenan (Publishing House of Wroclaw University of Economics and Business, 2021)
This study aimed to measure the short and long-term relation between female unemployment and the basic factors for society’s human development, namely education, health conditions and income levels, therefore it was important to test the effect of inflation in the equation which deals with unemployment. The study covered the years from 1990 to 2016, and used the United Nations Development Programme’s (UNDP) Human Development Index (HDI) to measure human development and the obtained real human development values for Turkey. To analyse the effects of real human development, information and communication technologies (ICT) and inflation on female unemployment, the Autoregressive Distributed Lag (ARDL) bounds test and the Engle–Granger test was used. As a result of the analysis, a reasonably strong, significant and negative relation was found between human development and female unemployment in the long term.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 225-252
Keywords: human development; female unemployment; ARDL bounds testing; Turkey